Світова глобалізація та міжкультурна комунікація у сфері освіти - Замета, М. О. (ХНУРЕ, 2025)
The article discusses the issues of mutual influence of world globalization and internationalization of higher education. It is proved that the process of world globalization is objective-historical and has a multifaceted character. It changes all spheres of life of modern mankind, including manifested in the field of education. International cooperation on academic exchanges and research programs with foreign universities is expanding, creating further opportunities for the internationalization of higher education. Globalization and internationalization of education bring economic profit, but as a result of these processes, problems of intercultural communication are aggravated.
Keywords: світова глобалізація; міжкультурна комунікація